Are women-only cars (WOC) a solution to groping? A survey among college students in Tokyo/Kanagawa, Japan - Shibata, Seiji (International journal of comparative and applied criminal justice, 2020)
This paper examines the groping of women in public transport in Tokyo/Kanagawa as well as its impact on victims. This research analyses riders’ perception of countermeasures against this sexual offence, in particular, women-only cars (WOC). The study is based on a survey conducted in June 2018 among college students in Tokyo/Kanagawa, Japan. Findings suggest that approximately 25% of women have experienced groping in the past three years, most often on trains than on buses. Victimised women perceive groping more often as a problem than those who have not been affected. Women-only cars are considered to be a suitable solution but not as effective as surveillance cameras or increased police patrols. Implications of the results for research and policy are discussed.